Assessing the Socio-Economic Impact of the Family Hope Program on Family Welfare in Jaranguda Village: A Mixed-Methods Evaluation - Marbun, Dina Sulastri; Anastasya, Susi; Miranda, Miranda (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2023)
This study delves into evaluating the impact of the Family Hope Program (PKH) on family welfare within Jaranguda Village, employing a comprehensive mixed-methods approach. Quantitative surveys and qualitative interviews were conducted to assess various welfare indicators, including income stability, education access, healthcare utilization, gender dynamics, and community engagement among beneficiary households. The findings reveal significant positive correlations between sustained program compliance and improvements in income levels, education attainment, healthcare utilization, and women's empowerment. Additionally, qualitative insights highlight broader socio-economic implications, emphasizing the program's role in community empowerment and social cohesion within the village. While validating PKH's efficacy, the study offers recommendations to enhance the program's impact, advocating for tailored interventions in education, healthcare, women's empowerment, and community engagement. The research contributes valuable insights for evidence-based policy-making and program enhancements, aiming to foster sustained socio-economic progress within vulnerable communities beyond Jaranguda Village.